2021
DOI: 10.56093/ijas.v91i9.116097
|View full text |Cite
|
Sign up to set email alerts
|

Automating yellow rust disease identification in wheat using artificial intelligence

Abstract: Plant disease has long been one of the major threats to world food security due to reduction in the crop yield and quality. Accurate and precise diagnosis of plant diseases has been a significant challenge. Cost-effective automated computational systems for disease diagnosis would facilitate advancements in agriculture. The objective of this paper is to explore computer vision based Artificial Intelligence method for automating the identification of yellow rust disease and improve the accuracy of plant disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Further, Jain et al (2021c) have reported that suitability identification should be followed by optimum area under allocation of suitable crops failing which may lead to over-exploitation of natural resources and unsustainability of the crop for the region. With advent of cheaper computational power and storage, latest machine learning based methods should also be explored for suitability analysis based on computer vision (Nigam et al 2021). The analysis clearly reveals that soil, climatic and topography parameters are essential parameters for crop suitability analysis.…”
Section: Integration Of Mce and Geospatial Techniquesmentioning
confidence: 99%
“…Further, Jain et al (2021c) have reported that suitability identification should be followed by optimum area under allocation of suitable crops failing which may lead to over-exploitation of natural resources and unsustainability of the crop for the region. With advent of cheaper computational power and storage, latest machine learning based methods should also be explored for suitability analysis based on computer vision (Nigam et al 2021). The analysis clearly reveals that soil, climatic and topography parameters are essential parameters for crop suitability analysis.…”
Section: Integration Of Mce and Geospatial Techniquesmentioning
confidence: 99%